Enhancing Moisture Damage Resistance in Asphalt Concrete: The Role of Mix Variables, Hydrated Lime and Nanomaterials - Adwar, Noor N.; Albayati, Amjad H. (Infrastructures (Basel), 2024)
Moisture-induced damage is a serious problem that severely impairs asphaltic pavement and affects road serviceability. This study examined numerous variables in asphalt concrete mixtures to assess their impact on moisture damage resistance. Mix design parameters such as the asphalt content (AC) and aggregate passing sieve No. 4 (PNo. 4) were considered as variables during this study. Additionally, hydrated lime (HL) was utilized as a partial substitute for limestone dust (LS) filler at 1.5% by weight of the aggregate in asphalt concrete mixtures for the surface layer. This study also investigated the potential enhancement of traditional asphalt binders and mixtures by adding nano-additives, specifically nano-silica oxide (NS) and nano-titanium dioxide (NT), at rates ranging from 0% to 6% by weight of the asphalt binder. To quantify the moisture damage resistance of the asphalt concrete mixes, two types of laboratory tests were employed: the tensile strength ratio (TSR) and the index of retained strength (IRS). The former characterizes moisture damage using tensile strength, whereas the latter uses compression strength. The physical properties of the asphalt binder, such as its penetration, softening point, and ductility, were also evaluated to identify the effects of the nanomaterials. The results indicated that variations in the mix design variables significantly affected the moisture damage resistance of the asphalt concrete mixtures. The maximum improvement values were obtained at the optimum asphalt content (OAC) and PNo. 4 (mid-range + 6%) with TSR values of 80.45 and 82.46 and IRS values of 74.39 and 77.14, respectively. Modifying asphalt concrete mixtures with 1.5% HL resulted in improved moisture resistance compared with mixtures without HL (0% HL) at each PNo. 4 level, reaching superior performance at PNo. 4 (mid-range + 6%) by 4.58% and 3.96% in the TSR and IRS tests, respectively. Additionally, both NS and NT enhanced the physical properties of the asphalt binder, leading to substantial enhancements in asphalt concrete mixture performance against moisture damage. A 6% dosage of NS and NT showed the best performance, with NS performing slightly better than NT. TSR was increased by 14.72 and 11.55 and IRS by 15.60 and 12.75, respectively, with 6% NS and NT compared with mixtures without nanomaterials (0% NM).